Phosphorus, Sulfur and Cobalt Fertilization Effect on Yield and Quality of Soybean (Glycine max L. Merrill) in Acidic Soil of Northeast India - BHATTACHARJEE, SARAJ; SINGH, A. K.; KUMAR, MANOJ; SHARMA, S. K. (Indian Journal of Hill Farming, 2014)
Soybean production on acidic soils of northeast India is often constrained by inadequate availability of phosphorus (P), sulfur (S) and cobalt (Co). To ascertain their individual and synergistic effects on growth, yield and quality of soybean, we conducted a field experiment on an acid alfisol (pH 4.5), with 12 treatments consisting of three levels of P (30, 60 and 90 kg P2O5 ha-1), two levels of S (15 and 30 kg S ha-1) and two levels of Co (1 and 2 kg Co ha-1) application in factorial combination. In general, growth and yield parameters of soybean responded positively to higher doses of P, S and Co applications, with the response to P fertilization being the best. Higher doses of P also improved seed protein content of soybean. Based on the results of this study, we conclude that 60 kg P2O5 ha-1 along with 15 kg S and 1 kg Co is advisable for optimum growth, yield and quality of soybean on acid alfisols of northeast India.